Prevalence of Staphylococcus aureus and Escherichia coli in soft cheeses from Ibarra’s markets - Salinas Tapia, Joseline Estefanía (2024)
The aim of this research is to identify the presence of E. coli, S. aureus, and coliforms in markets in Ibarra, located in Imbabura, Ecuador. A total of 30 samples of 100 grams of fresh cheese were collected from the most frequented markets in the city. From each sample, 25 grams were cultured on Compact Dry EC plates for E. coli and coliforms, and on Compact Dry XSA plates for S. aureus. Additionally, four control cheeses were prepared, including a negative control and controls infected with E. coli, S. aureus, and both pathogens. The data collected were compiled into a database containing columns for source, pH, CFU/ml of E. coli, CFU/ml of S. aureus, and CFU/ml of coliforms, which served as the basis for microbiological analysis. Spectral analysis was performed on the 30 market samples, the four control cheeses, and the isolated bacteria to identify spectral differences that could indicate the presence of pathogens using Raman spectroscopy with a 532 nm laser. Additionally, control samples were analyzed using FTIR. During microbiological analysis, microbial loads exceeding the limits set by INEN were detected, with no significant differences in pH or bacterial loads among the different markets. Furthermore, Raman spectroscopy revealed bacterial spectra, providing crucial information for the analysis and highlighting significant peaks associated with the bacteria.